E-Vision 2002, Shaping Our Future by Reducing Energy Intensity in the U.S. Economy, Volume I Proceedings of the Conference - Ortiz, David S. (RAND Corporation, 2003)
The E-Vision 2002 Conference, held in May 2002, was sponsored by the U.S. Department of Energy as a step toward implementing a key recommendation of the Bush administration's National Energy Policy. It gathered 150 of the nation's leading energy experts to discuss ways of reducing the country's energy intensity. This volume and the additional volume enclosed on CD-ROM contain the presentations and discussions that took place at the conference, including the identification of goals and the means to achieve them. It is a key work for those involved in implementing the National Energy Policy.